The Effect of Workload on Employee Performance at Plataran Indonesia - Jojo Jojo (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2025)
This study aims to examine the effect of workload on employee performance at Plataran Indonesia. Workload is one of the crucial factors that can influence the quality, productivity, and effectiveness of employee performance. Excessive workload may lead to stress, fatigue, and decreased motivation, while a balanced workload can improve effectiveness and achievement of organizational goals. This research employs a quantitative approach by distributing questionnaires to Plataran Indonesia employees as respondents. The collected data were analyzed using a simple regression analysis. The results of this study are expected to provide insights into the relationship between workload and employee performance, which can serve as a reference for Plataran Indonesia’s management in developing human resource strategies.